The Effect of Heat Tracing Installation for Wax Prevention on Onshore Buried Swampy Pipelines - Santoso, Samuel Bagas Wahyu; Sommeng, Andy Noorsaman; Dianita, Cindy (Jurnal Rekayasa Kimia & Lingkungan, 2024)
Transporting crude oil using pipelines is a widely adopted method globally. In one segment owned by PT. XYZ, especially in swampy areas, the fluid temperature tends to drop below the wax appearance temperature (WAT) during oil transportation. This is due to the relatively low temperature in swamp areas caused by heat loss to the environment. The solubility of paraffin in crude oil drastically decreases as fluid temperature drops, causing wax molecules to precipitate and deposit on the cold pipe walls. PT. XYZ employs chemical treatment by adding a pour point depressant (PPD) to lower the pour point temperature (PPT). However, PPD is effective only at certain temperatures, necessitating a study for alternative treatments. Another method involves installing heaters on the pipeline to reduce the viscosity of transported crude oil and enhance its flowability, either through direct heating or heat tracing using insulation with low thermal conductivity. Therefore, in PT. XYZ's case, an analysis is required to identify locations where fluid temperature decreases occur to ensure precise heater installation. Various software tools, including OLGA, have been developed to predict and describe wax deposition phenomena and temperature decreases along the pipeline. OLGA software can simulate locations of fluid temperature decreases in the pipeline, estimate heat loss along the pipeline, and simulate heat tracing technologies to prevent wax deposition. Simulation results indicate that wax deposition can be prevented by installing skin effect heat tracing with a heating power of 15 W/m and insulated with 2-inch aerogel, maintaining the oil temperature downstream at 157.34F, well above the desired 115F threshold.